ESRA19-0047 Ultrasound-guided bilateral erector spinae plane block versus intrathecal morphine for analgesia in living donors for liver transplantation: a randomized non-inferiority trial. (30th August 2019) - Kang, RA; Choi, DH; Ko, JS; Park, SJ; Kim, JS; Han Bum, J
Abstract : Background and aims: Preoperative intrathecal morphine (ITM) is an effective analgesic method for living liver donors after open hepatectomy, but there is several complications. the erector spinae plane (ESP) block has been reported to provide adequate postoperative analgesia in both thoracic and abdominal surgeries. We compared the postoperative analgesic efficacy of ESP block to ITM after laparoscopic living donor right hemihepatectomy. Methods: 54 living donors scheduled for laparoscopic right hemihepatectomy were randomly assigned to one of two groups: an ESP group ( n =27) and an ITM group ( n =27). Donors in the ESP group received preoperative ultrasound-guided bilateral ESP blocks at the level of T8 transverse process with an injection of local anesthetic (20 ml of 0.5% ropivacaine with 1:200, 000 epinephrine for each side). Donors in the ITM group received an intrathecal injection of morphine sulfate (400 µg) preoperatively. the primary outcome was the degree of analgesia assessed by 11-point numeric rating scale pain scores at 24 hours after surgery. the predetermined non-inferiority limit was 1. Results: The mean pain score at 24 hours postoperatively was 2.5±1.0 for ESP group and 1.3±1.1 for ITM group. the mean treatment difference (ESP−ITM) in pain score at 24 hours was 1.22 (95% CI: 0.66 to 1.79), and the upper limit of the 95% CI (1.79) was higher than the pre-specified non-inferiority margin (δ=1), indicating ESP was inferior to ITM. Conclusions: Ultrasound-guided bilateral ESP block may provide adequate postoperative pain control after living liver donor hepatectomy, but it showed comparably less analgesic efficacy than that of ITM during the first 24 hours.